New species and a new record of Isotomidae (Collembola) from the coast of Brazil - Abrantes, Eduardo Assis; de Mendonça, Maria Cleide (Zootaxa, 2007)
Two new isotomid species of the genera Archisotoma and Isotomodes and new record of Folsomides from Restinga de Maricá, Rio de Janeiro State, Brazil are presented.